Return logistics and process approach – dependencies and stages of creation - Huk, Katarzyna (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
Changes taking place in the economy as well as legal regulations influenced the development of return logistics. Currently, more and more products are returned to the recipient. Customer awareness, their growing requirements, online shopping, and thus the development of e-commerce, globalization are just some of the factors affecting the development of return logistics. To streamline operations and additional processes related only to returns logistics, the process approach is particularly helpful, namely the creation of process maps, which are instructions and guidelines for employees. The purpose of the article is to indicate the dependencies and stages of creating the mapping process in return logistics. Article is a theoretical and empirical and is based on the analysis of literature and conducted case studies.